Analisis Pengaruh NPM dan TATO terhadap Kinerja Laba pada Perusahaan Makanan & Minuman di BEI (2019–2023) - Wulandari Wulandari; Uhud Darmawan Natsir; Nurman Nurman; Muhammad Icwan Musa; Anwar Anwar (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to determine the effect of Net Profit Margin and Total Asset Turnover on Return On Asset (profit performance) on food & beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange. This study uses secondary data in the form of financial report data for each company for the period 2019-2023. Sampling was carried out using a purposive sampling technique and 10 companies were obtained that met the predetermined criteria. The analysis technique used in this study is quantitative analysis which calculates data from financial reports then uses SPSS tools to test and analyze data with calculations to draw conclusions. Hypothesis testing is carried out to determine whether there is an influence between the two variables. The results of the study stated that Net Profit Margin has a partial effect on Return On Asset, Total Asset Turnover does not have a partial effect on Return On Asset and Net Profit Margin and Total Asset Turnover simultaneously affect Return On Asset.